Eastern hemisphere - Salter, Christopher L. ([World geography], 2012)
Chapter 1. A geogpher's world -- Chapter 2. Planet Earth -- Chapter 3. Climate, environment, and resources -- Chapter 4. The World's people -- Chapter 5. History of the Fertile Crescent, 7000-500 BC -- Chapter 6. Judaism and Christianity, 2000 BC-AD 1453 -- Chapter 7. History of the Islamic World, AD 550-1650 -- Chapter 8. The Eastern Mediterranean -- Chapter 9. The Arabian Peninsula, Iraq, and Iran -- Chapter 10. Central Asia -- Chapter 11. History of Ancient Egypt, 4500-500 BC -- Chapter 12. History Ancient Kush, 2300 BC-AD 350 -- Chapter 13. History of West Africa, 500 BC-AD 1650 -- Chapter 14. North Africa -- Chapter 15. West Africa -- Chapter 16. East Africa -- Chapter 17. Central Africa -- Chapter 18. Souther Africa -- Chapter 19. History of Ancient India 2300 BC-AD 500 -- Chapter 20. History of Ancient China, 1600 BC-AD 1450 -- Chapter 21. The Indian Subcontinent -- Chapter 22. China, Mongolia, and Taiwan -- Chapter 23. Japan and the Koreas -- Chapter 24. Southeast Asia -- Chapter 25. The Pacific World -- Chapter 26. Early history of Europe, 2000 BC-AD 1500 -- Chapter 27. History of Early Modern Europe, 1500-1900 -- Chapter 28. Moder European history, 1900-today -- Chapter 29. Southern Europe -- Chapter 30. West-Central Europe -- Chapter 31. Northern Europe -- Chapter 32. Eastern Europe -- Chapter 33. Russia and the Caucasus.